2020
DOI: 10.3390/polym12051161
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Composite Scaffold Based on Naturally Derived Biomaterials

Abstract: This paper proposes the development of a biomimetic composite based on naturally derived biomaterials. This freeze-dried scaffold contains a microwave-synthesized form of biomimetic hydroxyapatite (HAp), using the interwoven hierarchical structure of eggshell membrane (ESM) as bio-template. The bone regeneration capacity of the scaffold is enhanced with the help of added tricalcium phosphate from bovine Bone ash (BA). With the addition of Gelatin (Gel) and Chitosan (CS) as organic matrix, the obtained composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…Hence, 1 L of simulated body fluid (SBF) solution was first prepared, based on the ionic species concentrations from Kokubo’s methodology [ 33 ] ( Table 2 ), corresponding to the ionic concentrations from human blood plasma, and following the steps previously described [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, 1 L of simulated body fluid (SBF) solution was first prepared, based on the ionic species concentrations from Kokubo’s methodology [ 33 ] ( Table 2 ), corresponding to the ionic concentrations from human blood plasma, and following the steps previously described [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hence, 1 L of simulated body fluid (SBF) solution was first prepared, based on the ionic species concentrations from Kokubo's methodology [33] (Table 2), corresponding to the ionic concentrations from human blood plasma, and following the steps previously described [34]. Small cylinders of 5 mm diameter, from each sample, were first weighed (determining the initial mass Wi), then completely soaked in 5 mL of SBF and maintained at 37 • C for various time periods.…”
Section: Swelling Ratio and Open Porositymentioning
confidence: 99%
“…Out of 71 relevant article titles collected from SCOPUS, PubMed, and Google Scholar, only 36 were included after screening the title, abstract, and content for in vitro degradation and cytotoxicity testing for the biocompatibility of eggshell-based hydroxyapatite. The articles came from several countries, such as India [ 11 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], Bangladesh [ 41 , 42 ], China [ 43 ], Korea [ 25 , 44 , 45 ], Turkey [ 46 , 47 , 48 ], Thailand [ 49 , 50 ], Brazil [ 26 ], Italy [ 51 ], USA [ 52 ], Romania [ 2 ], Vietnam [ 53 , 54 ], Colombia [ 55 ], and Egypt [ 56 ]. The study selection of the articles included in the systematic review is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Recovery usually requires the use of synthetic biomaterials [ 1 ]. Accidents and chronic illnesses cause bone defects that do not heal on their own, so the development of more efficient treatments is needed [ 2 ]. Porous biomaterials are scaffolds that are suitable for forming bone tissue and encouraging the diffusion of nutrients and metabolites out of cells and scaffolds [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, both natural and synthetic biomaterials have been employed for constructing scaffolds. This includes proteins like collagen [12,13], fibrin, silk; polysaccharides like chitosan, alginate, hyaluronic acid, etc. ; synthetic polymers like polylactic acid polycaprolactone.…”
Section: Introductionmentioning
confidence: 99%